Short-term weight gain after adenotonsillectomy in children with obstructive sleep apnoea: systematic review. Issue 3 (21st December 2015) - Van, M; Khan, I; Hussain, S S M
Abstract: Background: Children with obstructive sleep apnoea commonly undergo adenotonsillectomy as first-line surgical treatment. This paper aimed to investigate whether this intervention was associated with weight gain after surgery in the paediatric population with obstructive sleep apnoea. Method: Two independent researchers systematically reviewed the literature from 1995 to 2014 for studies on patients who underwent adenotonsillectomy with weight-based measurements before and after surgery. The databases used were Ovid Medline, Embase and PubMed. Results: Six papers satisfied all inclusion criteria. Four of these papers showed a significant weight increase and the others did not. The only high quality, randomised, controlled trial showed a significant increase of weight gain at seven months follow up, even in patients who were already overweight before their surgery. Conclusion: The current evidence points towards an association between adenotonsillectomy and weight gain in patients with obstructive sleep apnoea in the short term.